(untitled) (Journal of Rashid Latif Medical College, 2023)
Background: The HCV genotyping provides valuable epidemiological therapeutic information. It is rightly ratify the importance of genotype proficiency before clinical therapy. In the connection this particular study will be valuable for the health care providers and clinicians in designing the therapeutic strategies to cope this manic disease. The aim of the study is to investigate the prevalence of genotype present in District Bhimber. Materials and Methods: For this purpose 100 HCV antibody positive samples were collected and analyzed using Real Time PCR. Results: In our findings the prevalence of HCV in patients having age group greater than 40 was high. Most prevalent genotype is 3a 96(64%) followed by 1b 15(10%) and 3b 12(8%). 3а is found to be the prevalent genotype of the young patients and 1b among old patients. We have not found any correlation between viral load and gender. Intermediate viremia is seen in 3a genotype. Conclusion: It is also concluded that more work is needed in order to determine the genetic diversity and characterization of genotype among gender.